A Case Study of Principal-Agent Empowerment Relationship and Organizational Performance in the Oman Shipping Industry - Silva, Gajadeera Arachchige Ashan Bimal (2023)
The shipping industry in the global context is growing. This fact is further solidified via the exponential growth in the shipping industry in the Gulf region. However, based on a commonly used management tool, the BCG matrix, it has been identified that Gulf Agency Company (GAC) Oman’s organizational performance has declined, especially in the area of market share and profitability. Based on the above premise, this study proposal investigates the causal influence of agent empowerment on organizational performance to estimate the degree of the mediation of agent empowerment. Using a deductive research approach with a quantitative quasi-experimental design, this study aims to administer a survey with a sample of 98 respondents selected based on a random sampling method. The population represents senior managers, functional managers, and supervisors randomly chosen from four thousand GAC International Holdings employees. Data will be collected using a structured questionnaire with scales (1-5) to measure each item. Data will be recorded on Microsoft Excel 2019 and eventually uploaded to R-Studio (3.6.2 version) to analyze data to compute correlation, and hierarchical regression. Secondary data will be collected from organizational and industry-related sources about the last two years' annual sales turnover and market shares. The study findings suggest that the current relationship between the agent-principal is positively associated with organizational performance. However, the above relationship does not influence agent empowerment to contribute productively and meaningfully, and finally, agent empowerment does not have a causal effect on organizational performance. A few limitations associated with the study have been preidentified: the number of variables included for the investigation, sample size, and the time availability, as discussed in the antecedent sections.